Assessment of Myocardial Remodeling Using an Elastin/Tropoelastin Specific Agent with High Field Magnetic Resonance Imaging (MRI). Issue 8 (13th August 2015) - Protti, Andrea; Lavin, Begoña; Dong, Xuebin; Lorrio, Silvia; Robinson, Simon; Onthank, David; Shah, Ajay M.; Botnar, Rene M.
Abstract : Background: Well‐defined inflammation, proliferation, and maturation phases orchestrate the remodeling of the injured myocardium after myocardial infarction (MI) by controlling the formation of new extracellular matrix. The extracellular matrix consists mainly of collagen but also fractions of elastin. It is thought that elastin is responsible for maintaining elastic properties of the myocardium, thus reducing the risk of premature rupture. An elastin/tropoelastin–specific contrast agent (Gd‐ESMA) was used to image tropoelastin and mature elastin fibers for in vivo assessment of extracellular matrix remodeling post‐MI. Methods and Results: Gd‐ESMA enhancement was studied in a mouse model of myocardial infarction using a 7 T MRI scanner and results were compared to those achieved after injection of a nonspecific control contrast agent, gadolinium‐diethylenetriamine pentaacetic acid (Gd‐DTPA). In the infarcted tissue, Gd‐ESMA uptake (measured as R1 relaxation rate) steadily increased from day 3 to day 21 as a result of the synthesis of elastin/tropoelastin. R1 values were in good agreement with histological findings. A similar R1 behavior was observed in the remote myocardium. No mature cross‐linked elastin was found at any time point. In contrast, Gd‐DTPA uptake was only observed in the infarct with no changes in R1 values between 3 and 21 days post‐MI. Conclusions: We demonstrate the feasibility of in vivo imaging of extracellular matrix remodeling post‐MI using a tropoelastin/elastin binding MR contrast agent, Gd‐ESMA. We found that tropoelastin is the main contributor to the increased MRI signal at late stages of MI where its augmentation in areas of infarction was in good agreement with the R1 increase.